Relationship Marketing Techniques in Construction Projects: A Case Study - Davis, Peter (ARCOM, 2004)
Relationship Marketing (RM) embodies international, industrial and services marketing and in a business context is superseding traditional marketing theory. It is apparent from initial research into product and process industries that RM has the potential to provide construction organisations with significant benefits. These benefits include; enhanced ability to overcome problems, close coordination, process improvements; reduced risk associated with complex decision making and significant long-term value to prospective and existing clients. A summary of RM thinking is provided and three key variables being; trust, commitment and performance satisfaction are discussed. RM theory is conceptualised into a construction context using alliance procurement literature. The alliance literature gives pertinent insights into factors that afford potential project success. Finally three recent public sector case studies that have been documented are used to determine the validity of the theory using lessons learned reports.